Biology of the invertebrates - Pechenik, Jan A. (McGraw-Hill, 2015)
"This textbook is the most concise and readable invertebrates book in terms of detail and pedagogy (other texts do not offer boxed readings, a second color, end of chapter questions, or pronunciation guides). All phyla of invertebrates are covered (comprehensive) with an emphasis on unifying characteristics of each group."--Publisher's website